The Success Factors Women Entrepreneurship in The Digital Era - Edy Purwo Saputro, Edy; Irmawati, Irmawati (LPPM STIE EKA PRASETYA, 2024)
The success of entrepreneurial factors in the digital era is related to a number of factors, both internal and external. This is a challenge for the development of entrepreneurship and the purpose of this research is to find out the success factors that influence entrepreneurship by setting observations in Solo involving 100 respondents. Tests with regression analysis and the results illustrate that the entrepreneurship and economics variables have a positive effect on entrepreneurship while the innovation and technology variables have no effect. This finding promises further research despite its limitations